Pendampingan Arabic and English Club di Lingkungan Pondok Pesantren Alhamdulillah Berbaur Geger Kedungadem Bojonegoro - Ahmad Maujuhan Syah; Ahmad Zamar Kasyi; M. Fathoriq Alwi Shihab; Rohmawati Eka Safitri; Livil Ariati; Al Mas Khuzaimah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Every place or region must have hidden assets or potential which if used will have a huge impact on a place or region. The potential which is also an asset can be used to develop various sectors that support the development and quality improvement of a place or region, as well as the Alhamdulillah Berbaur Islamic Boarding School. However, in reality, most of these assets or potentials have not been developed properly, so it is very necessary to provide guidance or assistance in developing these assets by building a special community to learning English and Arabic. The purpose of this mentoring program is to develop the linguistic potential of the students of the Alhamdulillah Berbaur Islamic Boarding School, which in this case are Arabic and English which have not been well developed so far, this mentoring itself will focus on improving soft skills or basic Arabic and English skills. Through an asset-based community development approach or known as the ABCD Method, potential exploration can be carried out optimally by paying attention to various related aspects, which are then expected after the mentoring program ends the participants can become pioneers in establishing a conducive and productive Arabic and English environment. Disclosure of hidden assets using observation and interview methods reflects the ideals of Islamic boarding school managers and caregivers to graduates who have skills in communication in foreign languages to prepare themselves to become community leaders in the era of globalization